Menilai Kondisi Suatu Saham Dengan Pendekatan Price Earning Ratio Sebagai Dasar Keputusan Investasi. - Achmadtyar Fazrul Haq, Abidzar; Situngkir, Tiar Lina (Jurnal Riset Bisnis dan Investasi, 2022)
Stock investment is never separated from many risk threats, by valuating the stocks investor can minimize the risk in stock investment. The purpose of this research is to know how to find the intrinsic value of the stock, so we can know the condition of the stocks and make an investment decision. This research uses the Price Earnings Ratio approach to calculate the intrinsic value. The samples in this research are healthcare sector companies that are listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. The result of the Paired Sample t-Test there is no significant difference between market price and intrinsic value approached Price Earnings Ratio.